2021
DOI: 10.1186/s13326-021-00246-0
|View full text |Cite
|
Sign up to set email alerts
|

Toward a systematic conflict resolution framework for ontologies

Abstract: Background The ontology authoring step in ontology development involves having to make choices about what subject domain knowledge to include. This may concern sorting out ontological differences and making choices between conflicting axioms due to limitations in the logic or the subject domain semantics. Examples are dealing with different foundational ontologies in ontology alignment and OWL 2 DL’s transitive object property versus a qualified cardinality constraint. Such conflicts have to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The section editors' initial screening based on the title and abstract resulted in 326 papers. This set of papers was further reviewed jointly by the section editors to select a consensus list of 15 candidate best papers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The four top-ranked papers according to expert reviewers' evaluation were selected as the best papers in the field of KRM published in 2021 (see Table 1).…”
Section: Best Paper Selection For 2021mentioning
confidence: 99%
See 2 more Smart Citations
“…The section editors' initial screening based on the title and abstract resulted in 326 papers. This set of papers was further reviewed jointly by the section editors to select a consensus list of 15 candidate best papers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The four top-ranked papers according to expert reviewers' evaluation were selected as the best papers in the field of KRM published in 2021 (see Table 1).…”
Section: Best Paper Selection For 2021mentioning
confidence: 99%
“…In the second article, Keet and Grütter [7] proposed a framework to systematically handle modelling conflicts via meaning negotiation and conflict resolution in the ontology development and (re)use processes. They introduced a preliminary library of conflicts that may emerge during ontology authoring, and the conflict set data structure that stores the minimum necessary data about such conflicts.…”
Section: Best Paper Selection For 2021mentioning
confidence: 99%
See 1 more Smart Citation
“…Web Ontology Language (OWL) is one of the most prominent languages to represent ontologies. Since OWL is based on description logics, therefore it is a suitable option to represent and analyze knowledge of different domains [1][2][3][4][5][6][7]. The semantic representation of information by means of ontologies enables checking the consistency of the information as well as automatic reasoning to infer new knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking approaches to deal with the aforementioned problem, we found that the adoption of ontologies is a suitable option to represent and analyze knowledge of different domains [1][2][3][4][5][6][7]. The semantic representation of information by means of ontologies enables the consistency of the information to be checked, as well as automatic reasoning to infer new knowledge.…”
Section: Introductionmentioning
confidence: 99%